Issues Affecting Almajiri Schools in Nigeria: Water, Sanitation, and Hygiene (WASH) Parameters in Sokoto - Miya, Yusuf Yahaya; Abdul-Kareem, Jamil; Sa’eed, Abdullahi; Sarkingobir, Yusuf; Yabo, Aminu Musa; Bello, Zayyanu (Interdisciplinary Social Studies, 2023)
Background: There are many dimensions to the consequences of lack of sanitation, that are threat to public health. Diarrhea and relations due to poor WASH kills and put on cost on family and economy at large. Poor WASH affects economy in the sense that, millions of persons are unable to yield maximum productivity due to sickness, millions of working hours lost, and millions of schooling hours lost. Aim: This study performed an assessment of water, sanitation, and hygiene among Almajiri schools in Sokoto state, Nigeria. Method: A survey using a sample size of 300 schools gotten via simple random sampling, analyzed with descriptive statistics and chi-square test. Findings: The Almajiri schools surveyed, 3.3% of them have basic sanitation; 6.7% had limited sanitation; and most of them (90.0%) have no service at all (unimproved sanitation facilities or no sanitation facilities at the school). No Almajiri school had basic hygiene services (that is handwashing water and soap at the latrine vicinity), 33.7% had limited hygiene services, that is, they recorded acquiring of handwashing facilities with water but no soap available at the school at the time of the inspection, 66.6% of the schools had no services, that is no handwashing facilities or no water available at the school during the survey. Chi-square test has shown that there is significant difference in levels of water, sanitation, and hygiene among Almajiri schools in Sokoto state, Nigeria at p<0.05.